Analysis Factors Affecting the Income of Hybrid Corn Farming in Labuan District - Dafina Howara; Dewi Nur Asih; Alimudin Laapo; Wahyu Prianto; Sulmi Sulmi (CV. HEI PUBLISHING INDONESIA, 2025)
Hybrid corn is a leading commodity in Labuan District; however, farmers’ income varies due to production factors and farming conditions. The purpose of this study is to analyze the factors affecting the income of hybrid corn farming. Method: This research employed a quantitative approach using 81 hybrid corn farmer respondents selected through random sampling. Data were analyzed using multiple regression analysis through F-test, t-test, and R². The results of the regression analysis indicate that land area, production, and selling price significantly positively affect income, while production costs negatively affect it; however, irrigation availability does not have a significant effect. The regression model was simultaneously significant with an R² of 0.76, meaning that 76% of the income variation could be explained by the independent variables. The study recommends improving production cost efficiency, enhancing market access, and strengthening irrigation infrastructure.